Alternative Goals in Managing the Company in the Behavioural and Management Theories - Przybylska, Krystyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Defining company goals is one of the more difficult problems in the modern theory of firms. While such a goal has been clearly formulated in neoclassical theory (profit maximisation), in all modern conceptions it is difficult to find a consensus. A critical look at the neoclassical enterprise model has become the basis for the formulation of alternative business theories, such as managerial and behavioural theories. In these theories, two types of perception of objectives can be identified: theories assuming the existence of one main goal, other than the maximisation of profits (managerial theories) and theories assuming that companies implement a bundle of goals (behavioural theory).This article presents the main assumptions and ideas in managerial and behavioural theory in enterprise. This presentation is the basis for identifying the business objectives of companies that determine economic decision-making.